Hybrid Hierarchical Approach For Addressing Service Discovery Issues In MANETS. - Seno, Seyed Amin Hosseini; Wan, Tat-Chee; Budiarto, Rahmat (2007)

(untitled)
Management of Mobile Ad-hoc Net works (MANETs) is very difficult, because the movement of nodes is unpredictable, frequently changing the topology of the network Consequently, Service Discovery (SD) in the network a perquisite for efficient usage of network resources, is a complex problem.